Peculiarities of Evaluation of Motor Abilities Development in 10th-11th-Grade Boys - Старченко, В. М. (Physical Education Theory and Methodology, 2016)
The purpose of the research is to determine the main indicators of motor abilities development in the 10th-11th-grade boys. Materials and methods. To achieve the tasks set, the research relied on the following methods: analysis of scientific and methodological literature, pedagogical testing and methods of mathematical statistics. The participants in the study were 28 high-school boys (14 boys of the 10th-grade and 14 boys of the 11th-grade). Conclusions. The general level of motor readiness of the 10th-11th-grade boys is evaluated as average. The 10th-11th-grade boys showed statistically significant deviations in the tests intended to reveal their coordination abilities, relative strength and speed-strength abilities (p <0.05), which indicates a certain tendency to improve the general level of motor readiness and influence of the age-related peculiarities on the motor abilities development in high-school boys. By the level of functional readiness, the 10th-11th-grade boys belong to a group of healthy untrained boys. The informative indicators of the motor abilities development and functional readiness for the 10th-grade boys are the following tests: “Standing long jump”, “Shuttle run 4×9”, “Bending and unbending of arms from the lying position”, “Stange’s test”. For the 11th-grade boys such tests are “Standing long jump without visual control with efforts 2/3, error %”, “Evaluation of movement time parameters (5 s running)”, “Bent suspension”, and “Stange’s test”.